Persistent Anemia in the Setting of a Rare Pancreatic Pseudoaneurysm - Olivia Peralta; Christopher Chew; Matthew Newcomb (Case Reports in Gastrointestinal Medicine)
Introduction. Pancreatic pseudoaneurysm is a rare but potentially fatal complication that can follow pancreatitis. While early detection is critical to preventing poor long-term outcomes, clinical features vary significantly. Most often, abdominal pain is the presenting complaint, but this can be complicated as classic symptoms of pancreatitis also present with abdominal pain. Herein, we present a patient with an acute on chronic gastrointestinal bleed that was finally attributed to a pancreatic pseudoaneurysm. Case Presentation. The patient was a 56-year-old male with a past medical history significant for epilepsy, alcohol abuse, and hypertension who presented as a transfer from an outside facility for a gastrointestinal bleed. Prior to presentation, the patient reported rectal bleeding over the prior 1.5 months but had not sought care until bleeding increased along with increased abdominal pain. The patient’s hemoglobin was 6.3 at presentation of the outside facility and received a total of four units of packed red blood cells (PRBCs) prior to arrival. After arrival, persistent bleeding was noted, and an additional 2 units of PRBCs were transfused. A computed tomography angiography (CTA) of the abdomen was obtained to identify the source for embolization. This, however, revealed a 4 × 4 × 3.5 cm intrinsically dense or enhanced mass of the pancreatic head. Discussion. Pancreatic pseudoaneurysm is a rare but potentially fatal complication that can follow pancreatitis. In chronic pancreatitis patients who underwent imaging incidence is estimated to be up to 10%. Treatment is difficult, and coil embolization is often used, though this can lead to splenectomy due to splenic ischemia. Stent grafts can be used in the surrounding arteries to maintain the integrity of viscera but carry risk of stent-related thrombosis. Further research is needed on the optimal management of this potentially lethal complication of pancreatitis.